PERSEPSI GURU TERHADAP KOMPETENSI KEPRIBADIAN KEPALA SEKOLAH DI TANA TORAJA - Tadius Tadius; Suri Lembang (Universitas Muria Kudus, 2024)
The aim of this research is to determine the perceptions of elementary school teachers in Makale District, Tana Toraja regarding the personality competence of school principals. The research method used is quantitative research with a phenomenological approach. This research was carried out at UPT SDN 3 Makale, UPT SDN 5 Makale, UPT SDN 6 Makale, and UPT SD Kristen Makale 2. The research population was all elementary school teachers in Makale District, totaling 209 teachers. Determination of samples using the Slovin formula. The data analysis technique is carried out by processing all data that has been obtained in the field and then testing its validity so that reliable research results are obtained. The results of the research explain that teachers' perceptions of the personality competence of school principals in Tana Toraja, especially in Makale District, are very good. This is shown in the teacher's perception of the principal's personality competency where teacher recognition is at a percentage of 71% - 96% strongly agreeing with the statement given while agreeing at 8.8% - 47%. This means that the personality competency of the school principal is in accordance with the mandate of National Education Ministerial Decree No. 13 of 2017 concerning School/Madrasah Principal Standards.